Study Of Anthropometry, Sedentary Lifestyle, And Neck Disability Of Physiotherapy Students In Bali - Made Hendra Satria Nugraha; Anak Ayu Nyoman Trisna Narta Dewi; Anak Agung Gede Angga Puspa Negara; Ni Wayan Bintang Mida Suputri (Interest : Jurnal Ilmu Kesehatan, 2022)
Background: The COVID-19 pandemic situation has caused a crisis that affects all aspects of human life, including education. Students conduct online learning in front of laptops for a long enough duration. There is the potential for changes in anthropometric measurements (body size) during the pandemic and the possibility of a decrease in neck function. This study was conducted to determine the anthropometric description, level of sedentary lifestyle, and neck functional ability of physiotherapy students at the Faculty of Medicine, Udayana University during the Covid-19 pandemic. Methods: This study is an analytic observational study with cross-sectional method. The study was conducted from July to August 2021 and data collection was carried out online. The research subjects were 156 people consisting of physiotherapy students from Udayana University who were listed on the list of active Physiotherapy students at Udayana University who had filled out the research questionnaire that had been provided. Results: In male respondents, it was found that 78.4% (n=29) had a normal waist circumference (≤90cm) while for female respondents 80.7% (n=96) had a normal waist circumference (≤80cm). The results of the body mass index found that 48.1% (n=75) were classified as normal. A total of 58.3% (n=91) of respondents had non-sedentary behavior. In the assessment of the level of neck disability, respondents in the category of no disability were 57.7% (n=90). Conclusion: Based on the results and discussion, it can be concluded that waist circumference for both men and women is dominated by the normal category, sedentary behavior by the non-sedentary category, and neck functional ability by the non-disabled category.